Bibliometric Mapping of Research on Career Selection of Students in South Asia: A Comparative Study of Publication Dynamics, Impact of Citations, and Collaboration Networks (2021–2025) - Karki, Tej Bahadur; Radha, P; Khadka, Kalpana; Lamichhane, Basu Dev (NPRC Journal of Multidisciplinary Research, 2026)
Introduction: Career selection among students is an important factor that determines their success in professional life, economic stability, and general well-being. The global research literature has seen remarkable growth over the years, but the synthesis of knowledge in various disciplinary and geographical regions has not followed suit. Bibliometric studies on this issue are still rare, especially for developing countries like Nepal.Methods: This study conducted a systematic bibliometric and thematic analysis of the student career selection literature published between 2021 and 2025. A Boolean search string—`("career selection" OR "career choice" OR "vocational choice") AND ("student" OR "undergraduate" OR "graduate")`—was applied to title and abstract fields in Dimension.ai. Filters included publication year (2021–2025), document type (Article), Open Access (Gold), and Non-APC journals, yielding 290 included studies. Publication trends, citation patterns, country and institutional contributions, collaboration networks (Total Link Strength), and thematic content (word cloud) were analysed.Results: Publication output rose from 41 (2021) to 83 (2025), whereas the proportion of cited publications fell from 73.17% to 19.28%. Citations expanded exponentially from 13 to 214. Brazil (18 papers), Australia (15), and Indonesia (18) were highly productive, and the Philippines demonstrated the highest citation efficiency (38 citations for 2 publications). There was little international collaboration (most countries had Total Link Strength ≤1). The word cloud validated the prominence of "student," "career," "choice," and "decision" terms. The Nepalese context highlighted substantial deficits: foreign employment preference, mismatch between curriculum and labor market requirements, and scarcity of humanities, engineering, and creative arts studies.Conclusion: The field is expanding yet becoming more fragmented with reduced citation scope and negligible international cooperation. Nepal needs tailor-made career development models, curriculum changes responsive to labor market trends, and cross-disciplinary research on psychological, socio-economic, and organizational factors that affect students' career choices.